2019
DOI: 10.1097/qad.0000000000002119
|View full text |Cite
|
Sign up to set email alerts
|

Prior exposure to thymidine analogs and didanosine is associated with long-lasting alterations in adipose tissue distribution and cardiovascular risk factors

Abstract: Background: Thymidine analogues (TA) and didanosine (ddI) have been associated with redistribution of body fat from subcutaneous (SAT) to visceral (VAT) adipose tissue, which, in turn, is a risk factor for cardiovascular disease (CVD). We explored differences in adipose tissue distribution between people living with HIV (PLWH) with prior exposure to TA and/or ddI, without exposure, and uninfected controls and the association with CVD risk factors. Methods: 761 PLWH from the COCOMO study and 2,283 age-and sex-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…The long-lasting lipodystrophic phenotype associated with previous use of thymidine NRTIs results in a higher risk of hypertension, high TC and reduced HDL [1,5]. Truncal adiposity is clearly related to a dysmetabolic phenotype with increased risk of CVD and diabetes and also of liver steatosis.…”
Section: Consequences and Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…The long-lasting lipodystrophic phenotype associated with previous use of thymidine NRTIs results in a higher risk of hypertension, high TC and reduced HDL [1,5]. Truncal adiposity is clearly related to a dysmetabolic phenotype with increased risk of CVD and diabetes and also of liver steatosis.…”
Section: Consequences and Managementmentioning
confidence: 99%
“…PLWH from the AGEhIV cohort have higher waist circumference and lower hip circumference than wellpaired non-infected individuals [4] and fat redistribution was associated with higher rates of hypertension [5]. In addition, in the COCOMO study, previous cumulative exposure to stavudine, zidovudine or didanosine is associated with long-lasting increased visceral adipose tissue (VAT) and decreased subcutaneous adipose tissue (SAT), as evaluated by abdominal CT scan, and related with excess risk of hypertension, high total cholesterol (TC) and low HDL [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thymidine analogues (TA) and didanosine (ddI) have known deleterious effect on adipose tissue metabolism [1]. Previous results from our group suggested that prior use of TA and ddI in people living with HIV (PLWH) is associated with alterations in body fat distribution, particularly loss of subcutaneous (SAT) and accumulation of visceral adipose tissue (VAT) [1], even years after treatment discontinuation. This phenotype is known to be associated with increased of cardiometabolic risk.…”
Section: Introductionmentioning
confidence: 99%